2014
DOI: 10.7448/ias.17.4.19615
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of HIV‐1 drug resistance in treatment‐naïve patients and its clinical implications in an antiretroviral treatment program in Cameroon

Abstract: IntroductionFacing the rapid scale-up of antiretroviral treatment (ART) programs in resource-limited settings, monitoring of treatment outcome is essential in order to timely detect and tackle drawbacks [1].MethodsIn a prospective cohort study, 300 consecutive patients starting first-line ART were enrolled between 2009 and2010 in a large HIV treatment centre in rural Cameroon. Patients were followed up for 12 months. Virologic failure was defined as a VL >1000 cop/mL at month 12. Besides CD4 and viral load (VL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…The present study detected moderated levels (11.1 %) of TDR which was higher than the 7.3% and 7.55% recorded in the Centre region of Cameroon [7,11] and10.4 % from rural and urban towns in Cameroon [23]. However, it was lower than the 13.9% from the South west region [24], and 18.8% from rural villages in Cameroon [17]. In addition TDR rates ranging from 4.9%-8% has also been recorded in children [15,23] in pregnant women [25] from Cameroon.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The present study detected moderated levels (11.1 %) of TDR which was higher than the 7.3% and 7.55% recorded in the Centre region of Cameroon [7,11] and10.4 % from rural and urban towns in Cameroon [23]. However, it was lower than the 13.9% from the South west region [24], and 18.8% from rural villages in Cameroon [17]. In addition TDR rates ranging from 4.9%-8% has also been recorded in children [15,23] in pregnant women [25] from Cameroon.…”
Section: Discussioncontrasting
confidence: 72%
“…In Cameroon, studies have shown that there is increasing prevalence of TDR over time and ranging from 1 to 10.4% [15][16][17]. Nevertheless, these studies were designed only for a particular locality like Centre, and Littoral regions.…”
Section: Introductionmentioning
confidence: 99%
“…18 Diversified factors were associated with ART failure in general and with the virological failure in particular. 19,20 Factors that determine ART outcome may differ from one context to another. Therefore, understanding factors that determine the virological failure among patients on ART is important to inform HIV/AIDS prevention and control program stakeholders.…”
Section: Plain Language Summarymentioning
confidence: 99%
“…These determinants were among those reported in studies in in the country and in other similar African countries. 19,20,[23][24][25][26][27] Under the assumptions, calculation using the variable "five year or more duration on ART" gave largest sample size; that was 504 and consequently, 252 cases and 252 controls were included in this study.…”
Section: Sample Size Determination and Sampling Proceduresmentioning
confidence: 99%
“…The proportion for ARVs was 4.2% [2]. People with HIV exposed to subtherapeutic ARVs are at increased risk of developing HIV drug resistance [3,4]. Continued vigilance to ensure use of quality ARVs is critical for three reasons.…”
Section: To the Editor-mentioning
confidence: 99%